Small is Sustainable (and Beautiful!) – Encouraging European Smaller Enterprises to be Sustainable. - Grayson, David; Dodd, Tom (Cranfield School of Management, 2007)
This paper takes stock of the some of the significant progress made and lessons learned in supporting the uptake of corporate social responsibility (CSR) amongst small and medium-sized enterprises (SMEs). It then identifies a number of issues that we think merit further attention as this important work continues.